Impact of new foam surfactant blend with water alternating gas injection on residual oil recovery - Memon, M.K. (Springer Verlag, 2017)
Enhanced oil recovery methods are the future of maximizing oil recoveries. Any incremental oil recovery can support the world economy by producing more oil at a minimum price. The surfactants are the major constituent of the injection fluids for EOR applications. Addition of foam-generated surfactants in water alternating gas injection is one of the potential solutions for reducing the gas mobility and improving sweep efficiency, but the major challenge of surfactants used with water alternating gas injection is its stability in presence of formation water and crude oil at reservoir conditions. The objective of this study is to investigate the stable surfactant as a foaming agent to improve the efficiency of residual oil and reduce the gas mobility. To achieve this main objective, individual and new surfactant blended formulations were evaluated with injection water and crude oil in the porous media at 96 °C and 1400 psi. Experimental result showed that generated foam in presence of crude oil has reduced gas mobility which provides good indication of CO2 mobility control and improves sweep efficiency. Oil recovery based on original oil-in-place by surfactant blend of 0.6 wt AOS + 0.6 wt TX 100, 0.6 wt AOS + 0.6 wt LMDO and individual surfactant of 0.6 wt AOS were recorded as 91.9, 83.7 and 72.66, respectively. Foam stability in presence of crude oil, reduction in gas mobility and increase in oil recovery indicated that these surfactant blends are good foaming agents as compared to individual surfactant in enhanced oil recovery applications. © 2016, The Author(s).